2019
DOI: 10.1590/1678-4162-10430
|View full text |Cite
|
Sign up to set email alerts
|

Identification of equine herpesvirus type 1 as cause of abortion in mares in Southern Brazil

Abstract: Identification of equine herpesvirus type 1 as cause of abortion in mares in Southern Brazil [Identificação do herpesvirus equino tipo 1 como causa de abortos em éguas no sul do Brasil]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Despite performing IHC to detect HVE-1 in fetal tissues in all cases, no positive result was observed. The low frequency of viral abortion in horses in southern Brazil was reported by Marcolongo-Pereira et al (2012) and Estima-Silva et al (2019), being possibly associated with the use of efficient vaccines (Schlafer 2004, Marcolongo-Pereira et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Despite performing IHC to detect HVE-1 in fetal tissues in all cases, no positive result was observed. The low frequency of viral abortion in horses in southern Brazil was reported by Marcolongo-Pereira et al (2012) and Estima-Silva et al (2019), being possibly associated with the use of efficient vaccines (Schlafer 2004, Marcolongo-Pereira et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no samples from aborted fetuses were sent to our laboratory for diagnosis, and serology for EHV-1 was not performed and other non-viral etiologies could not be ruled out. However, several reports have demonstrated the presence of specific antibodies against EHV-1 in horses in Brazil (Alencar-Araripe et al 2014, Diaz et al 2015, Estima-Silva et al 2019 and further studies to investigate the possible association of different types of equine herpesviruses causing reproductive, respiratory, neurological and ophthalmic disorders, should be made in country.…”
Section: Discussionmentioning
confidence: 99%
“…Another types of herpesvirus are known causing distinct diseases and clinical signs in horses: equid alphaherpesvirus 1 (EHV-1), genus Varicellovirus, causing abortions in mares and also keratoconjunctivitis, encephalomyelitis, and neonatal pneumonia (Léon et al 2008, Dubale 2017, Estima-Silva et al 2019, Dunuwille et al 2020; equid gammaherpesvirus 2 (EHV-2), genus Percavirus, that has been found in horses with keratoconjunctivitis, gastroesophageal ulcers, and chronic throat lesions (Agius & Studdert 1994, Kershaw et al 2001, Cicolo et al 2019, Taulescu et al 2021; equid alphaherpesvirus 4 (EHV-4), genus Varicellovirus, an important cause of acute and fatal rhinopneumonithis in fowls and occasionally associated with equine abortions (Crabb & Studdert 1995, Gerst et al 2003; and equid gammaherpesvirus 5 (EHV-5), genus Percavirus, the cause of a severe and progressive syndrome of pulmonary fibrosis in adult horses (Verryken et al 2010, Williams et al 2013, Marenzoni et al 2015, Gulati et al 2019. A sixth virus, equid alphaherpesvirus 9 (EHV-9), genus Varicellovirus can cause subclinical encephalitides in horses, but until to date the disease was described just under experimental conditions (Hussey et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Between 1994 and 2012, outbreaks occurred in southern Brazil. During this outbreak, one pregnant mare out of 50 had an abortion (Estima-Silva et al, 2019). The prevalence of EHV-1 in mares and foals was 26.2% by Stasiak et al (2020) describe an outbreak of abortions in Arabian mares at a well-managed State stud farm in Poland.…”
Section: The Equ Ine Herpe S Virus T Ype-1 (Ehv-1) Introductionmentioning
confidence: 94%
“…Between 1994 and 2012, outbreaks occurred in southern Brazil. During this outbreak, one pregnant mare out of 50 had an abortion (Estima‐Silva et al, 2019). The prevalence of EHV‐1 in mares and foals was 26.2% and 11.4%, respectively, while the seropositivity for EHV‐1 was 52.48% in Turkey (Yildirim, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%